A cluster of central retinal artery occlusions following cataract surgery - Sen, Alok; Mitra, Ashish; Tripathi, Shubhi; Sharma, Megha; Shenoy, Pratik (Indian journal of ophthalmology, 2019)
Purpose: To report a series of central retinal artery occlusions (CRAO) following cataract surgery complicated by posterior capsular rupture (PCR). Methods: Data from 14 patients with acute CRAO following cataract surgery was collected for this study including subject demographics, initial and final best-corrected visual acuity, systemic investigations, optical coherence tomography (OCT) and fundus fluorescein angiography (FFA) findings. Results: Mean subject age was 59.9 ± 12.1 years. Male: Female ratio was 1:1. All patients were operated between October and November 2015 and presented with acute vision loss 1 to 4 days after surgery. All the patients underwent cataract surgery under peribulbar anesthesia and had PCR for which anterior vitrectomy (AV) was done. In all the cases Ethylene oxide (ETO) sterilized vitrectomy probe was used for AV. Clinical picture of CRAO was noted in all the cases during the immediate postoperative period. OCT showed inner retinal layer hyperreflectivity while FFA was normal in all the cases. The final visual acuity was poor in all the eyes. This paper discusses the possible mechanisms of CRAO in these cases. Conclusion: CRAO is a potential complication of peribulbar anesthesia for intraocular surgery in patients with vascular risk factors and hence any substance that can aggravate the vasospasm in such patients should be used cautiously. Vasospasm could be caused by ETO as residual ETO could be present in the vitrectomy machine tubing causing toxicity. It is recommended to be cautious while using ETO sterilized instruments for cataract surgery.